Kondisi Sosial Ekonomi Pekerja Sektor Informal Pada Kawasan Car Free Day Di Kota Jambi - Yoranda Seftiani; Heriberta .; Nurhayani .; Siti Hodijah (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the social and economic characteristics of workers, as well as examine the factors that influence the income and performance of informal sector workers in the Car Free Day (CFD) area of ​​Jambi City. The informal sector in the CFD has been proven to provide flexible employment for the community. Data were collected through questionnaires from 96 respondents and processed using descriptive statistics and Multiple Linear Regression. Descriptive results show that the worker profile is dominated by women (57.30%), having a final education level of high school (64.60%), and evenly distributed across all age groups. These characteristics indicate that the informal CFD sector is a major support for female workers and individuals with secondary education. Furthermore, the results of the inferential analysis indicate that business capital, working hours, and the number of family members have a significant influence on workers' income. These findings recommend the need for local government interventions focused on business management training and increasing access to capital to optimize the economic welfare of informal sector workers.